Binding of Tetracyclines to Acinetobacter baumannii TetR Involves Two Arginines as Specificity Determinants - Sumyk, Manuela; Himpich, Stephanie; Foong, Wuen Ee; Herrmann, Andrea; Pos, Klaas M.; Tam, Heng-Keat (Frontiers in Microbiology, 2021)
Acinetobacter baumannii is an important nosocomial pathogen that requires thoughtful consideration in the antibiotic prescription strategy due to its multidrug resistant phenotype. Tetracycline antibiotics have recently been re-administered as part of the combination antimicrobial regimens to treat infections caused by A baumannii. We show that the TetA(G) efflux pump of A. baumannii AYE confers resistance to a variety of tetracyclines including the clinically important antibiotics doxycycline and minocycline, but not to tigecycline. Expression of tetA(G) gene is regulated by the TetR repressor of A. baumannii AYE (AbTetR). Thermal shift binding experiments revealed that AbTetR preferentially binds tetracyclines which carry a O-5H moiety in ring B, whereas tetracyclines with a 7-dimethylamino moiety in ring D are less well-recognized by AbTetR. Confoundingly, tigecycline binds to AbTetR even though it is not transported by TetA(G) efflux pump. Structural analysis of the minocycline-bound AbTetR-Gln116Ala variant suggested that the non-conserved Arg135 interacts with the ring D of minocycline by cation-π interaction, while the invariant Arg104 engages in H-bonding with the O-11H of minocycline. Interestingly, the Arg135Ala variant exhibited a binding preference for tetracyclines with an unmodified ring D. In contrast, the Arg104Ala variant preferred to bind tetracyclines which carry a O-6H moiety in ring C except for tigecycline. We propose that Arg104 and Arg135, which are embedded at the entrance of the AbTetR binding pocket, play important roles in the recognition of tetracyclines, and act as a barrier to prevent the release of tetracycline from its binding pocket upon AbTetR activation. The binding data and crystal structures obtained in this study might provide further insight for the development of new tetracycline antibiotics to evade the specific efflux resistance mechanism deployed by A. baumannii.